CIPP evaluation of project based P5 implementation for holistic student development - Angelina Meta Taurista; Markus Budiraharjo (Research and Development in Education (RaDEn), 2025)
The Pancasila Student Profile Strengthening Project, henceforth P5,  is a program designed to foster students' holistic development in alignment with the Pancasila Student Profile dimensions. Nevertheless, there is an absence to expose the attainment of all dimensions, particularly in SMAN 1 Kalasan. This study investigates the implementation of the P5 under the “Social Work” program to explore how it promotes students’ holistic growth within all dimensions of the Pancasila Student Profile. This study applied a qualitative approach and thematic analysis and data were gathered from student reflections, facilitator interviews, classroom observations, and program documents. The evaluation was guided by the CIPP evaluation model (Context, Input, Process, Product), integrated with Project-Based Learning (hereafter PjBL) elements.  As a result of all dimensions accomplishment in SMAN 1 Kalasan, the researchers elaborated six themes appeared; spiritual and ethical growth in local contexts, empowerment through role ownership and voice, support systems and school culture for P5, inclusive collaboration and cultural awareness, inquiry-driven action and thoughtful decision making, and creativity and innovation in real world expression. In addition, by combining the CIPP framework and PjBL principles, the research proposes an innovative evaluation tool for measuring holistic educational outcomes and strengthening P5 implementation in school contexts.